If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y(x + 9) + -2(x + 9) = 0 Reorder the terms: Y(9 + x) + -2(x + 9) = 0 (9 * Y + x * Y) + -2(x + 9) = 0 (9Y + xY) + -2(x + 9) = 0 Reorder the terms: 9Y + xY + -2(9 + x) = 0 9Y + xY + (9 * -2 + x * -2) = 0 9Y + xY + (-18 + -2x) = 0 Reorder the terms: -18 + 9Y + -2x + xY = 0 Solving -18 + 9Y + -2x + xY = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 9Y + -2x + 18 + xY = 0 + 18 Reorder the terms: -18 + 18 + 9Y + -2x + xY = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 9Y + -2x + xY = 0 + 18 9Y + -2x + xY = 0 + 18 Combine like terms: 0 + 18 = 18 9Y + -2x + xY = 18 Add '2x' to each side of the equation. 9Y + -2x + 2x + xY = 18 + 2x Combine like terms: -2x + 2x = 0 9Y + 0 + xY = 18 + 2x 9Y + xY = 18 + 2x Reorder the terms: -18 + 9Y + -2x + xY = 18 + 2x + -18 + -2x Reorder the terms: -18 + 9Y + -2x + xY = 18 + -18 + 2x + -2x Combine like terms: 18 + -18 = 0 -18 + 9Y + -2x + xY = 0 + 2x + -2x -18 + 9Y + -2x + xY = 2x + -2x Combine like terms: 2x + -2x = 0 -18 + 9Y + -2x + xY = 0 The solution to this equation could not be determined.
| 2x(2x+1)=5 | | 15-24x+11x= | | 14+8n=4n+6n | | 6(1+3x)=-120 | | 4x^2+12x=7 | | 6k-8+6=-2+k | | 3(3.3-1)=9 | | 37(x-148)=74 | | 15x+21=36-36x+24 | | 0=x^2+x-e^4 | | 4(7-6x)=-116 | | 8k=10k+12 | | -72+X^2+-1x=0 | | 7/x-6-3/4x-24 | | y=5x^2-10x+37 | | 8x^2+16x^9-28x^4+20= | | 8(3-n)=88 | | 245=5(6k+7) | | 4/x+28 | | -x^2-9x-2=0 | | 88=-2n+7(4n-6) | | y=x^2+16x+17 | | -8(4v-5)=296 | | p=23 | | 5-(-2+27)= | | 4(-7+4b)=-108 | | -3y+2x=-5x+5 | | 15=z-342 | | 2=r/12+3 | | 4n-6=n+9 | | -8(a+4)=-88 | | 11=7+x/2 |